2011
DOI: 10.1111/j.1365-2699.2011.02588.x
|View full text |Cite
|
Sign up to set email alerts
|

An arctic community of symbiotic fungi assembled by long‐distance dispersers: phylogenetic diversity of ectomycorrhizal basidiomycetes in Svalbard based on soil and sporocarp DNA

Abstract: Aim Current evidence from temperate studies suggests that ectomycorrhizal (ECM) fungi require overland routes for migration because of their obligate symbiotic associations with woody plants. Despite their key roles in arctic ecosystems, the phylogenetic diversity and phylogeography of arctic ECM fungi remains little known. Here we assess the phylogenetic diversity of ECM communities in an isolated, formerly glaciated, high arctic archipelago, and provide explanations for their phylogeographic origins.Location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 92 publications
4
126
1
1
Order By: Relevance
“…Plants as well as ECM fungi from glacial refugia would be the sources of organisms for these communities. Therefore, measuring the ECM fungal community structure in the Northern Hemisphere can help identify the refugia and better understand species dispersal, species survival, speciation, and the history of ecological niche transitions (Geml et al 2010, 2012). In this aspect, due to their ubiquity in natural ecosystems, species in the genus Russula should be able to provide excellent information from which to understand these issues.…”
Section: Emerging Directionsmentioning
confidence: 99%
“…Plants as well as ECM fungi from glacial refugia would be the sources of organisms for these communities. Therefore, measuring the ECM fungal community structure in the Northern Hemisphere can help identify the refugia and better understand species dispersal, species survival, speciation, and the history of ecological niche transitions (Geml et al 2010, 2012). In this aspect, due to their ubiquity in natural ecosystems, species in the genus Russula should be able to provide excellent information from which to understand these issues.…”
Section: Emerging Directionsmentioning
confidence: 99%
“…Bahram et al (2012) found evidence for host range expansions of local symbionts, including sebacinoids, to distantly related host taxa in exotic Pinus sylvestris plantations in relation to native host trees, Carpinus betulus, Fagus orientalis, and Quercus castaneifolia, in the Hyrcanian forests of Iran. Based on molecular evidence, Geml et al (2012) concluded that longdistance dispersal of some ECM fungi, including Sebacina species in the Northern Hemisphere, may have played a major role in their phylogeographic history. Human-caused introductions of ECMs are common and widespread, and may exceed 200 species (Vellinga et al 2009).…”
Section: Sebacinalean Ectomycorrhizae (Ecm)mentioning
confidence: 99%
“…In addition to these traditional studies European Arctic-alpine fungal communities have been studied by high throughput sequencing (e.g. Bjorbaekmo et al 2010, Fujiyoshi et al 2011, Lentendu et al 2011, Geml et al 2012, Botnen et al 2014. Also the Arctic region of Greenland has been relatively well studied mycologically (Borgen et al 2006).…”
Section: Introductionmentioning
confidence: 99%